Significance of platelet parameters in pre-eclampsia: A prospective cross-sectional study from a tertiary care center in North India - Amrutha Aravind; Poonam Khambra; Sonam Sharma (Asian Journal of Medical Sciences, 2025)
Background: Pre-eclampsia is a life-threatening disorder that develops after 20 weeks of gestation and is a major cause of maternal morbidity and mortality worldwide. Platelet activation plays a crucial role in its pathogenesis, contributing to end-organ damage. Platelet parameters such as platelet count, mean platelet volume (MPV), platelet distribution width (PDW), and plateletcrit (PCT) are indirect markers of platelet activation and can be evaluated during routine hematological analysis.